Arterial Line Management: An Evidence-Based Guide for Healthcare Professionals (The Review of Diabetic Studies, 2024)
Background: Arterial catheterization is a cornerstone in critical care and perioperative medicine, enabling continuous blood pressure monitoring and frequent arterial blood sampling. Despite its clinical utility, the procedure carries risks such as infection, thrombosis, and ischemia, necessitating evidence-based management strategies.Aim: To provide a comprehensive review of arterial line indications, anatomy, insertion techniques, complications, and best-practice maintenance protocols to enhance patient safety and optimize outcomes.Methods: This narrative review synthesizes current evidence and clinical guidelines on arterial line management, focusing on site selection, sterile technique, ultrasound guidance, equipment readiness, and multidisciplinary roles. Literature sources include peer-reviewed studies and consensus recommendations.Results: Radial artery cannulation remains the preferred site due to accessibility and collateral circulation, while femoral and brachial sites are reserved for specific clinical contexts. Ultrasound guidance significantly improves first-pass success and reduces complications. Infection prevention hinges on maximal sterile barriers and disciplined maintenance, while neurovascular monitoring mitigates ischemic risk. Reported complication rates range from 10–13% in adults and approximately 10% in pediatrics, with infection and thrombosis being most common. Interprofessional collaboration—particularly nursing and pharmacy involvement—strengthens safety and efficacy.Conclusion: Arterial line management requires a structured, indication-driven approach integrating technical precision, infection control, and vigilant monitoring. Ultrasound guidance, standardized protocols, and team-based care reduce complications and preserve the clinical benefits of invasive hemodynamic monitoring.